Assessment of phytochemicals, antioxidant and antimutagenic activity in micropropagated plants of Quercus serrata, a high value tree species of Himalaya. (3rd September 2018) - Pandey, Aseesh; Sekar, K. Chandra; Tamta, Sushma; Rawal, R. S.
Abstract: The major aim of the present study was to: (i) develop an efficient clonal in vitro propagation procedure, and (ii) investigate and compare phytochemicals, antioxidant, and DNA damage protection activity in methanolic extracts of in vitro raised and mother plant leaves of Quercus serrata . The study succeeded in establishing an efficient clonal micropropagation procedure using nodal segments taken from in vivo growing mother plant. The WP medium supplemented with six-benzyleaminopurine (BAP: 8.88 μM) plus indole-3-acetic acid (IAA: 1.43μM) produced the highest number of shoots/explant having maximum average shoot length. In vitro derived shoots exhibited best rooting upon application of 100μM indole-3-butyric acid for 48 h. Among studied phytochemicals, the total phenol content was recorded higher from in vitro raised plants and total flavonoid in the mother plant. Antioxidant activities were recorded higher in case of in vitro raised plants. Also, the methanolic leaf extract of in vitro raised plants exhibited higher antimutagenic activity that of mother plant. These findings indicate Q. serrata as a promising source of natural antioxidants that could be utilized commercially for the prevention of photoaging and oxidative stress-mediated skin diseases.